2018
DOI: 10.1016/bs.ai.2018.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Chemokines: Critical Regulators of Memory T Cell Development, Maintenance, and Function

Abstract: Memory T cells are central to orchestrating antigen-specific recall responses in vivo. Compared to naïve T cells, memory T cells respond more quickly to cognate peptide:MHC with a shorter lag time for entering the cell cycle and exerting effector functions. However, it is now well established that this enhanced responsiveness is not the only mechanism whereby memory T cells are better equipped than naïve T cells to rapidly and robustly induce inflammation. In contrast to naïve T cells, memory T cells are compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 79 publications
(129 reference statements)
0
16
0
Order By: Relevance
“…Taken together, several models have been proposed for the generation of memory T lymphocytes. It is conceivable that more than one of these models contribute to memory T cell development in vivo, and may be influenced by factors such as TCR signal strength and inflammatory conditions in the microenvironment (cytokines), and in addition, costimulatory signals (e.g., CD28 family) [77] and other environmental cues, such as chemokines and even the microbiota from the tissue in which a T cell is activated [78][79][80].…”
Section: T-bet the Master-regulator Of Th1 Cells Acts In An Expressmentioning
confidence: 99%
“…Taken together, several models have been proposed for the generation of memory T lymphocytes. It is conceivable that more than one of these models contribute to memory T cell development in vivo, and may be influenced by factors such as TCR signal strength and inflammatory conditions in the microenvironment (cytokines), and in addition, costimulatory signals (e.g., CD28 family) [77] and other environmental cues, such as chemokines and even the microbiota from the tissue in which a T cell is activated [78][79][80].…”
Section: T-bet the Master-regulator Of Th1 Cells Acts In An Expressmentioning
confidence: 99%
“…In addition, and similar to Rubcn -/- macrophages, Rubcn -/- DCs significantly upregulated pro-inflammatory cytokines and chemokines, compared to Rubcn +/+ DCs (Martinez et al, 2011a; Martinez et al, 2016b). Specifically, Rubcn -/- DCs upregulated factors known to promote CD8 + T cell recruitment (such as Ccl2 , Ccl3 , Ccl4 , Cxcl9 , and Cxcl10 ) and activation (such as Il1b , Il6 , Il12b , and Tnf ) (Figure 1C, S1E) (Rahimi and Luster, 2018; Turner et al, 2014). Consistent with previous reports (Hayashi et al, 2018), Rubcn -/- DCs produced less IFNβ than Rubcn +/+ DCs (Figure 1C, S1E).…”
Section: Resultsmentioning
confidence: 99%
“…Chemokines and chemokine receptors are implicated in the mobilization and localization of immune cells to peripheral tissues and the generation of memory response. [21][22][23] While a role for CXCR6 in CD8 + T cell resident memory responses has been reported in infectious disease models, [24][25][26] there are no studies that directly address if specific chemokine receptors facilitate resident memory response by driving localization or retention of CD8 + T cells in cancerous tissues. Our current study addresses this gap and identified CXCR6 as the predominant chemokine receptor expressed by CD8 + Trm cells in human ovarian cancer, and their presence in tumors is associated with increased survival.…”
Section: Introductionmentioning
confidence: 99%